Multi-Sensor Fusion Technology Based on Aircraft: The Implementation of Aircraft State Monitoring - Bai Zirun; Xia Zixuan (MATEC Web of Conferences)
Multi-sensor fusion technology has become a core element in developing modern Multi-sensor fusion technology, which has become a crucial component in advancing the modern aviation industry. It combines data from multiple sources to enhance flight safety and awareness of the aircraft’s state. Aviation industry. It integrates multi-source data to improve flight safety and state awareness. This thesis describes the advances in the application of this technology to aircraft condition monitoring and provides insights into the key challenges encountered by multi-sensor fusion technology in existing aircraft. Such as the explosive growth of data scale and the credibility of sensor data, and prospectively discusses the future development direction of this technology, focusing on the potential application of artificial intelligence and big data technology in the field of multi-sensor fusion to provide theoretical support for the optimization of the aviation safety monitoring system.